Experience with NORM waste disposal in different European countries - Gellermann, Rainer; Caplin, Helen; Chambers, Nick; Dongen, Oskar van; Grandia, Fidel; Hondros, Jim; Kunze, Christian; Michalik, Boguslaw; Pepin, Stéphane; Rovenska, Katerina N; Trevisi, Rosabianca (Radiation protection dosimetry, 2023)
Industrial processes generate various quantities of waste that can be contaminated with radionuclides of natural origin (naturally occurring radioactive material ('NORM waste')). The efficient management of this waste is essential for any industries affected by NORM waste generation. To obtain an overview of current practices and approaches in Europe, the IRPA Task Group on NORM conducted a survey among task group members and other experts from European countries. The results revealed significant differences in methods and approaches in the European countries. In many countries, landfills are used to dispose of small- and medium-sized quantities of NORM waste with limited activity concentration. But our survey indicated that despite a uniform reference basis for national legislation in Europe, there are different framework conditions for the disposal of NORM waste in practice. In some countries, the disposal is hampered because the interface between the radiation protection system and the waste regime is not yet clearly regulated. Particular practical problems include the lack of acceptance of waste because of the 'radioactivity' stigma and only vague specifications by the legislators on acceptance obligations of the waste management sector.
Keywords: Refuse Disposal; radiační ochrana; odpadky - odstraňování; Waste Management; nakládání s odpady; Europe; Evropa; Industry; Radiation Protection; průmysl